2021
DOI: 10.1002/sres.2808
|View full text |Cite
|
Sign up to set email alerts
|

Systems thinking assessments in engineering: A systematic literature review

Abstract: Engineers, facing increasingly complex problems, need to understand the technical and contextual aspects of their work to develop effective solutions. Assessments of comprehensive systems thinking skills are needed to support the development of these skills and to inform professional placement. Thus, our study investigated current systems thinking assessments in engineering by systematically reviewing existing assessments. We analyzed which systems thinking skills were emphasized, how they were evaluated, how … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
1
11
0
Order By: Relevance
“…Further, data support the notion that once key habits of thinking are mastered, regardless of the context, learners tend toward more sophisticated thinking when new contexts are encountered (Mambrey et al, 2020). When it comes to assessment of this type of thinking, there is a gap in terms of how we measure both technical and contextual aspects of systems thinking (Dugan et al, 2022).…”
Section: Defining Systems Thinkingsupporting
confidence: 52%
“…Further, data support the notion that once key habits of thinking are mastered, regardless of the context, learners tend toward more sophisticated thinking when new contexts are encountered (Mambrey et al, 2020). When it comes to assessment of this type of thinking, there is a gap in terms of how we measure both technical and contextual aspects of systems thinking (Dugan et al, 2022).…”
Section: Defining Systems Thinkingsupporting
confidence: 52%
“…Whilst there are clear examples of studies exploring ST with cognitive neuroscience tools (i.e., through concept mapping and the use of fNIRS) in a laboratory setting (e.g., Hu et al, 2019 ) to our knowledge there is no research to date exploring the relationship between ST and observational learning and/or the use of CSA practices involving mobile neuroscience tools/measures in an LIC. A recent systematic literature review on systems thinking in engineering found that the triangulation of ST via multiple assessment types such as the use of concept mapping and fNIRS (Hu and Shealy, 2018 ) is likely to be beneficial (Dugan et al, 2022 ). To this end, we have proposed using NIRS and concept mapping similar to the approach taken by Hu and Shealy ( 2018 ) and the use of FCM which therefore provides several forms of triangulation ( Figure 2 ).…”
Section: Proposed Theory Of Change (Toc) and Limitationsmentioning
confidence: 99%
“…Dugan et al (2022) conducted a systematic review of ST assessment in the field of engineering. This study investigated the ongoing ST assessment in engineering by a systematic review of existing assessments.…”
Section: Literature Review and Backgroundmentioning
confidence: 99%